Effiacy and safety of metronomic chemotherapy versus palliative hydroxyurea in unfit acute myeloid leukemia patients: A multicenter, open-label randomized controlled trial - Saranya Pongudom (2020)
© 2020 Asian Pacific Organization for Cancer Prevention. Background: Management of unfi AML patients is a therapeutic challenge. Most hematologists tend to avoid aggressive treatment leaving patients with a choice of best supportive care. We hypothesized that metronomic chemotherapy could be an alternative treatment for unfi AML patients. Methods: A multi-center randomized controlled trial was conducted in seven university-affiiated hospitals in Thailand. Unfi AML patients were recruited and followed up from December 2014 to December 2017. Patients were randomly assigned to receive either metronomic chemotherapy or palliative hydroxyurea. Overall survival rates were compared using Cox's proportional hazard survival analysis. Results: A total of 81 eligible patients were randomly allocated and included for ITT analysis. The OS rate was higher in group receiving metronomic chemotherapy than in group receiving palliative treatment at 6 and 12 months with borderline signifiance (6 months HR 0.60; 95%CI 0.36, 1.02; p-value 0.060; 12 months: HR 0.66; 95%CI 0.41, 1.08; p-value 0.097). Conclusion: Metronomic chemotherapy could prolong survival time of unfi AML patients, especially in the fist 12 months after diagnosis without increasing treatment-associated adverse events.